Universalitas Islam dan Lokalitas Budaya dalam Bingkai Islam Nusantara - Ishom Fuadi Fikri (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2018)
Islam has both universal and particular dimension, where the universality of Islam is reflected in the maqāṣid al-sharī‘ah, i.e., public benefits, whereas the Islamic particularity deals with practical aspects of the Islamic law in human life, including local cultures. This means that the presence of Islam does not aim to eliminate human cultures. Rather it serves as a universal value that is able to permeate and accommodate various local cultures. The universality of Islam and the cultural locality should not be in, somehow, an opposite way. Instead, they should be in a dialectical and even an affirmative relation. Employing the deductive-descriptive method, this article aims to reveal the discourse of Islam Nusantara on the aspects of Islam’s universality and the cultural locality in Indonesia. Islam Nusantara is a sociological term for the manifestation of Islam’s universality, which has been absorbed into the particularity of local cultures in Nusantara. The article will further argue that Islam’s encounter and the local cultures in Indonesia have created a uniquely indigenous model of understanding, comprehension, and practice of the Islamic doctrines. Therefore, Islam Nusantara’s notion should make the Indonesian Muslims able to synergize Islam and nationalism within a frame called ‘Indonesia and diversity’.